189k views
3 votes
Solve the equation. \dfrac5{13}=t-\dfrac{6}{13} 13 5 ​ =t− 13 6 ​ start fraction, 5, divided by, 13, end fraction, equals, t, minus, start fraction, 6, divided by, 13, end fraction t=t=t, equals

2 Answers

4 votes

Answer:


t=(11)/(13)

Explanation:


(5)/(13) = t -(6)/(13)

Add
(6)/(13) to both sides.


(5)/(13) + (6)/(13) = t -(6)/(13) + (6)/(13)


(11)/(13) =t

User Ayres
by
5.9k points
4 votes

Answer:

11 /13 = t

Explanation:

5/13 = t -6/13

Add 6/13 to each side

5/13 + 6/13 = t -6/13+ 6/13

11 /13 = t

User Rashedcs
by
5.3k points